Comparison of rectangular and triangular fins when condensation occurs - Toner, M.; Kiliç, A.; Onat, K. (Springer Science and Business Media LLC, 1983)
In this study rectangular and triangular fins have been compared when condensation occurs. The temperature distributions and the heat transfer found using quasilinearization techniques and those found by using Gauss-Seidel iteration method are compared and this approximation proved to be quite satisfactory. The fin temperature and the fin effectiveness of the triangular and rectangular fins have been determined with and without condensation and optimum fin dimensions have been given as a function of Biot number.